Integrated digitization method for cultural heritage objects - Mączkowski, Grzegorz; Sitnik, Robert; Krzesłowski, Jakub (Photonics Letters of Poland, 2012)
Digitization of cultural heritage objects recently becomes very promising tool for storing information about precious artifacts. This work shows an integrated, multimodal measurement method for digitization of cultural heritage objects with the example of representative metal figurine. We propose an optical measurement system which uses structure light projection, multispectral color acquisition and Bi-Directional Reflectance Distribution Function (BRDF) estimation. Accordingly an implementation of data processing path is explained with illustration of its main steps and a final result. Full Text: PDF References J. Portal, Q. Duan, The First Emperor: China's Terracotta Army, British Museum Press (2007) N. Yastikli, "Documentation of cultural heritage using digital photogrammetry and laser scanning", Journal of Cultural Heritage 8(4), 423-427 (2007)[CrossRef] J. Salvi,"Pattern codification strategies in structured light systems", Pattern Recognition 37(4), 827-849 (2004)[CrossRef] S. Tosovic, R. Sablatnig, M. Kampel, Proc. of 7th Computer Vision Winter Workshop 2, 108-118 (2002) R. Sitnik, M. Kujawinska, J. Woznicki,"Digital fringe projection system for large-volume 360-deg shape measurement", Opt. Eng. 41, 443-449 (2002)[CrossRef] F. Chen, G.M. Brown, M. Song,"Overview of three-dimensional shape measurement using optical methods", Opt. Eng. 39(1), 10 (2000)[CrossRef] W. Mocko, "Color measurements using digital photography", Przeglad Elektrotechniczny 83(1), 39-42 (2007) E. A. Marszalec, M. Pietikaeinen,"Color measurements based on a color camera", Proc. SPIE 3101, 170, (1997)[CrossRef] A. Mansouri, A. Lathuilière, F. S. Marzani, Y. Voisin, P. Gouton,"Toward a 3D Multispectral Scanner: An Application to Multimedia", [CrossRef] F. H. Imai, M. R. Rosen, R. S. Berns, "Comparison of spectrally narrow-band capture versus wide-band with a priori sample analysis for spectral reflectance estimation", Proc. Eighth Color Imaging Conference, 234 (2000) F. H. Imai, M. R. Rosen, R. S. Berns, "Multi-spectral imaging of a van Gogh's self-portrait at the National Gallery of Art, Washington, D.C.", PICS conference, IS&T, 185–189 (2001) G. Mączkowski, R. Sitnik, J. Krzesłowski, "Integrated Method for 3D Shape and Multispectral Color. Measurement", J. of Im. Sci. and Tech. 55(3), 030502-(10) (2011) F.E. Nicodemus,"Directional Reflectance and Emissivity of an Opaque Surface", Appl. Opt. 4(7), 767-773 (1965)[CrossRef] J.F. Blinn,"Models of light reflection for computer synthesized pictures", ACM SIGGRAPH Computer Graphics 11(2), 192-198 (1977)[CrossRef] H. Zhang, Z. Wu, Y. Cao, G. Zhang, "Measurement and statistical modeling of BRDF of various samples", Optica Applicata 40(1), 197-208 (2010) S. R. Marschner, S. H. Westin, E.P. Lafortune, K.E. Torrance,"Image-Based Bidirectional Reflectance Distribution Function Measurement", Appl. Opt. 39(16), 2592-2600 (2000)[CrossRef] J. Krzesłowski, R. Sitnik, G. Mączkowski,"Integrated three-dimensional shape and reflection properties measurement system", Appl. Opt. 50(4), 532-541 (2011)[CrossRef] B. Phong,"Illumination for computer generated pictures", Communications of the ACM, 18, 311-317, (1975)[CrossRef] R. Sitnik, M. Karaszewski, "Automated processing of data from 3D scanning of cultural heritage objects", Digital Heritage. 28-41, (2010) G. Wyszecki, W.S. Stiles, Color Science: Concepts and Methods, Quantitative Data and Formulae. John Wiley & Sons, New York (2000) R. Sitnik, J. Krzesłowski, G. Mączkowski,"Archiving shape and appearance of cultural heritage objects using structured light projection and multispectral imaging", Opt. Eng. 51, 021115, (2012)[CrossRef] R. Sitnik, M. Kujawińska,"From reality to virtual reality: 3D object imaging techniques and algorithms", Proc. SPIE 5146, 54–61 (2003)[CrossRef] P.J. Besl, N.D. McKay,"A method for registration of 3-D shapes", IEEE Transactions on Pattern Analysis and Machine Intelligence 14(2), 239–256 (1992)[CrossRef] R. Sitnik, G. Mączkowski, J. Krzesłowski, "Calculation methods for digital model creation based on integrated shape, color and angular reflectivity measurement", Digital Heritage, 13–27 (2010) R. Sitnik, J. Krzesłowski, G. Mączkowski,"Processing Paths from Integrating Multimodal 3D Measurement of Shape, Color and BRDF", International Journal of Heritage in the Digital Era 1, 25-44 (2012)[CrossRef] IEC 61966-2-1:1999: Multimedia systems and equipment. Colour measurement and management. Colour management. Default RGB colour space. sRGB